The Big Five Personality Traits And Their Relationships With Leading Change, Leadership Styles And Effectiveness Of Malaysian Managers - Y.A.Abujarad, Ismael (2007)
This study was conducted to investigate the influence of the Big Five Dimensions of personality of the Malaysian Managers and the leadership styles these managers use on their leadership effectiveness and leading change. Total sample of 105 managers was used in this study. The majority of these managers use consultative leadership style; however, some use autocratic, democratic and some of them use laissez-fair. The results of this study showed that Extroversion was significantly and positively related with Leading Change.